Javanese Prosocial Behavior in The Rewang Tradition - Hanin Dhiya Ramadhanti; Firratu Tsaqifa; Nabila Nabila (Universitas Ahmad Dahlan, 2023)
Perilaku Prososial Masyarakat Jawa dalam Tradisi RewangJavanese culture gave birth to many local wisdoms and traditions that have been passed down from generation to generation until today. One of the traditions that is maintained and is still often found is the rewang tradition. The rewang tradition is a form of prosocial behavior in Javanese society which is carried out with the aim of helping community members who have a purpose in the form of marriage. This study aims to understand and describe the prosocial behavior of the Javanese community in the rewang tradition. The method used in this research is a qualitative method with the data collection technique used is literature study. The research results obtained in this study indicate that the rewang tradition can be seen as a form of prosocial behavior carried out by the Javanese community. This can be explained by looking at the motives and factors that cause the emergence of prosocial behavior.